Sexually transmitted diseases in homosexual and bisexual males from a cohort of human immunodeficiency virus negative volunteers (Project Horizonte), Belo Horizonte, Brazil - L Lignani Jr; EI Oliveira; M Carneiro; M Greco; J Andrade; CM Antunes; DB Greco (Memorias do Instituto Oswaldo Cruz, 2000)
Sexually transmitted diseases (STD) are very frequent in the whole world. Males who do not use a condom during their sexual relations are at great risk. We report cases of STD during six months of observation, among homosexual/bisexual males who participate in the Project Horizonte. There were 16 cases of genital warts, 6 cases of human immunodeficiency virus infection, 24 cases of unspecific urethritis, 28 cases of herpes simplex virus infection, 30 cases of syphilis, 58 cases of gonorrhea and 84 cases of pediculosis. We concluded that a condom must be used in all sexual relations and new counseling techniques are needed, to avoid this situation.